Microstructure and mechanical properties of friction stir welded joints made from ultrafine grained aluminium 1050. (25th December 2015) - Lipińska, Marta; Olejnik, Lech; Pietras, Adam; Rosochowski, Andrzej; Bazarnik, Piotr; Goliński, Jacek; Brynk, Tomasz; Lewandowska, Małgorzata
Abstract: In order to obtain ultrafine grained structure, commercially pure aluminium (Al 1050) plates were subjected up to 8 passes of Incremental Equal Channel Angular Pressing (IECAP) following route C. Plates in different stages of IECAP were joined using Friction Stir Welding (FSW). All welded samples were investigated to determine their mechanical properties and structure evolution in the joint zone. The joining process reduced mechanical strength of material in the nugget zone, which was explained by the grain growth resulting from temperature rise during FSW. Nevertheless, the obtained results are promising in comparison to other methods of joining aluminium. Graphical abstract: Highlights: Ultrafine grained Al 1050 plates with enhanced mechanical properties were produced using incremental ECAP, route C. The plates were successfully joined using friction stir welding and good quality joints were obtained. The welding process caused grain growth in stir zone but the mechanical strength of welds is higher than of annealed Al.